AL-HADS AS AN EPISTEMOLOGY OF ISLAMIC PSYCHOLOGY - Argo, Basuki Setyo; Syukur, Suparman; Sulthon, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The background of this research lies in the ongoing debate regarding the epistemological foundations of Islamic psychology. Purpose: The aim of this study is to analyze the role of *al-hads* (intuition) as an epistemology in Islamic psychology, assessing its relevance as a source of knowledge in understanding the human psyche. Method: This research adopts a qualitative approach with a literature review and conceptual analysis methodology, involving the examination of classical and contemporary texts within Islamic thought, particularly those related to *bayani*, *burhani*, and *'irfani*. Result: The results show that *al-hads*, in the form of revelation or intuition, can be considered a source of absolute truth in Islamic psychology, while *al-hads* in the form of personal inspiration or intuition, distinct from prophetic revelation, is more relative and dependent on individual experience. Conclusion: The study concludes that although *al-hads* is often regarded as irrational or unscientific, it can serve as a valid epistemological foundation in Islamic psychology, where the relationship between reason and intuition enables a more holistic approach to understanding psychological dynamics in accordance with Islamic teachings.